Evaluation of seed qnaIi$y in long-staple cotton (Gossypium brerbadense) - OBASI, M O; MSAAKPA, T S (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2000 and 2001 cropping seasons to study the variability among 30 cultivars of long-staple cotton (Gossypium barbadense L.) for 5 seed cotton quality traits, viz oil percentage, iodine value, refractive index, protein percentage and seed index. Correlation coefficient among these 5 traits were also studied to choose the high seed quality cultivars for effective use in the breeding programme. Combined analysis over the 2 seasons showed significant differences among all traits for the studied cultivars. Only years significantly affected both oil percentage and iodine value. Year x cultivars interaction was not significant for all traits indicating that the cultivars responded the same from year to year. Significant negative correlation was noted between protein percentage and seed index (-0.36) and between protein percentage and oil percentage (-0.38). A significant positive correlation was obtained between refractive index and iodine value (+0.92). On the other hand protein and oil levels among the 30 cultivars were not significantly associated with refractive index and iodine value